Pelayanan pembuatan akta kelahiran menuju transformasi digital di kabupaten Bogor - R.Oetje Subagdja (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Because it is impossible to reject the use of technology in public service procedures, the Bogor Regency Population and Civil Registration Service has implemented digital transformation in its operations, including the issuance of birth certificates. Knowing how digital transformation is implemented in the Bogor Regency Dukcapil Office is the aim of this research. This research applies Royyana's thesis (2021) which states that digital transformation is a shift for all institutions involving five indicators: technology adoption, process, structure, human resources and strategy. Bogor Regency Disdukcapil employees act as research informants in this qualitative descriptive research design. The findings of this research can show that the Bogor Regency Dukcapil Office has succeeded in implementing digital transformation.